Training of Trainers (ToT) on Pest and Disease Management in Agriculture under Climate Change Course Module - Sorho, Fatogoma; Kone, Daouda; Ekepu, David (2025)
The Training of Trainers (ToT) workshop on Pest and Disease Management in Agriculture under Climate Change, delivered virtually from 25–28 March 2025, aimed to strengthen the capacity of university lecturers, researchers, and practitioners across Africa to integrate climate-smart approaches into agricultural education and practice. The module, developed under the AICCRA–RUFORUM–WASCAL collaboration, introduced participants to the impacts of climate change on abiotic stressors and climate-sensitive pests and diseases affecting crops, livestock, poultry, and aquaculture systems. A total of 87 participants (with 32% female and 68% male) from 25 countries attended the training, with 45 completing the post-training evaluation survey. Results show high satisfaction with the relevance, structure, and interdisciplinary focus of the module, as well as strong appreciation for the expertise of facilitators. Participants reported significant gains in understanding integrated pest and disease management, climate-smart agriculture (CSA), and early warning systems, with 86.7% expressing willingness to deliver the module within their institutions. Key participant recommendations include extending the training duration, incorporating more case studies and interactive elements, and expanding access through multilingual and hybrid delivery formats. Overall, the ToT contributed meaningfully to building a community of practice equipped to disseminate climate-resilient pest and disease management strategies across African universities and agricultural systems.